Diversity and temporal distribution of Fusarium oxysporum f. sp. vasinfectum races and genotypes as influenced by Gossypium cultivar - Dyer, David R.; Newman, Molli; Lawrence, Kathy S. (Frontiers in Fungal Biology, 2022)
Fusarium wilt of cotton, caused by Fusarium oxysporum f. sp. vasinfectum (FOV), is a global disease of cotton. Multiple races and genotypes of FOV have been documented infecting cotton and inducing symptoms of wilting, stunting, vascular discoloration, and plant death. This study was initiated in the National Cotton Fusarium Wilt Evaluation Field to 1) assess the population diversity of FOV races/genotypes infecting cotton cultivars which were selected for either FOV or Meloidogyne incognita resistance or susceptibility and to 2) to determine the in-season temporal variability of these FOV races/genotypes. Symptomatic plants were collected from the field in each trial from two weeks after planting until crop defoliation in 2018 and 2019. The race/genotype of each FOV isolate collected was identified by sequencing portions of the translation elongation factor, β-tubulin, and the phosphate permease genes. In total, eight races/genotypes of FOV were collected throughout the three site years. FOV race 1 was the most predominant in all tests (AUDPC=101.1); statistically higher numbers of isolates from LA-108 (AUDPC=59.9), race 8 (AUDPC=47.5), and race 2 (AUDPC=38.6) were also found compared to other races and genotypes collected. The genotypes MDS-12, LA-110, and LA-127/140 were found in all tests but at a low incidence, and LA-112 was only found in small numbers (three isolates) in one 2019 test. A positive correlation was observed between the accumulation of growing degree days and FOV race 1, race 2, race 8, LA-108, and LA-110.